YOUTH OF POLAND AND UKRAINE IN THE CONDITIONS OF COVID-19 PANDEMIC: MENTAL HEALTH STATUS AND THE LEVEL OF NEUROTISM - Długosz, Piotr; Kryvachuk, Liudmyla (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the results of research on neuroticism among students in Poland and Ukraine, which was given rise by the coronavirus pandemic. The research was conducted on a sample of 1978 respondents in Poland and 411 in Ukraine with the use of the on-line survey method. The scale of neuroticism comprises of 8 items. The following symptoms have been included in the scale: headaches; stomach aches; dizziness; trouble sleeping; nervousness; gloom, bad mood; fatigue; irritability, bad mood. The intensification of symptoms in the last 7 days was measured with the use of the ordinal scale. All statistical analyses have been conducted using the SPSS, version 25. The research results indicate that average and high levels of neuroticism were observed among 61% of the respondents in Poland and 47% in Ukraine. The comparison of results between the Polish and Ukrainian youth indicates that Ukrainians have a lower level of neuroticism than Poles, which may mean that they cope with the quarantine and distant learning better. Regression analysis has shown that the main factors which have impact on the level of neuroticism are educational burnout, gender, financial situation, interest in the pandemic and satisfaction with life. Neuroticism increases together with the educational burnout, the loss of economic resources and the increase in the interest in the pandemic. Moreover, females scored higher on the scale of neuroticism. Comparative analyses between Polish and Ukrainian students indicate that Ukrainian youth cope with the quarantine and distance education better and have better mental health. The collected observations show that in the conditions of pandemic a neurotic generation of coronavirus may come to being. To sum up, it may be said that in both countries the difficulties connected with distant learning, the fear of the pandemic, gender and financial standing have impact on the level of neuroticism. It seems that together with the quarantine, the worsening of mental condition took place.